A mild phenotype associated with KCNQ1 p.V205M mediated long QT syndrome in First Nations children of Northern British Columbia: effect of additional variants and considerations for management - Bene Watts, Simona; Gauthier, Barbara; Erickson, Anders C.; Morrison, Julie; Sebastian, Mavis; Gillman, Lawrence; McIntosh, Sarah; Ens, Connie; Sherwin, Elizabeth; McCormick, Rod; Sanatani, Shubhayan; Arbour, Laura (Frontiers in Pediatrics, 2024)
Introduction: Congenital Long QT Syndrome (LQTS) is common in a First Nations community in Northern British Columbia due to the founder variant KCNQ1 p.V205M. Although well characterized molecularly and clinically in adults, no data have been previously reported on the pediatric population. The phenotype in adults has been shown to be modified by a splice site variant in KCNQ1 (p.L353L). The CPT1A p.P479L metabolic variant, also common in Northern Indigenous populations, is associated with hypoglycemia and infant death. Since hypoglycemia can affect the corrected QT interval (QTc) and may confer risk for seizures (also associated with LQTS), we sought to determine the effect of all three variants on the LQTS phenotype in children within our First Nations cohort. Methods: As part of a larger study assessing those with LQTS and their relatives in a Northern BC First Nation, we assessed those entering the study from birth to age 18 years. We compared the corrected peak QTc and potential cardiac events (syncope/seizures) of 186 children from birth to 18 years, with and without the KCNQ1 (p.V205M and p.L353L) and CPT1A variants, alone and in combination. Linear and logistic regression and student t-tests were applied as appropriate. Results: Only the KCNQ1 p.V205M variant conferred a significant increase in peak QTc 23.8ms (p<0.001) above baseline, with females increased by 30.1ms (p<0.001) and males by 18.9ms (p<0.01). There was no evidence of interaction effects with the other two variants studied. Although the p.V205M variant was not significantly associated with syncope/seizures, the odds of having a seizure/syncope were significantly increased for those homozygous for CPT1A p.P479L compared to homozygous wild type (Odds Ratio [OR]3.0 (95% confidence interval [CI] 1.2-7.7); p=0.019). Conclusion: While the KCNQ1 p.V205M variant prolongs the peak QTc, especially in females, the CPT1A p.P479L variant is more strongly associated with loss of consciousness events. These findings suggest that effect of the KCNQ1 p.V205M variant is mild in this cohort, which may have implications for standard management. Our findings also suggest the CPT1A p.P479L variant is a risk factor for seizures and possibly syncope, which may mimic a long QT phenotype.